Effect of Glucose on Plasma Glucagon, Growth Hormone, and Insulin in Exchange Transfusion. Issue 252 (April 1972) - Milner, R. D. G.; Fekete, M.; Assan, R.; Hodge, J. S.
Abstract : Exchange transfusions were performed on term normal-for-dates, and term small-for-dates infants using blood preserved with acid citrate and glucose or acid citrate alone. The plasma concentrations of glucose, free fatty acids, glycerol, insulin, glucagon, and growth hormone were measured in the donor blood and in blood from the infant at different times during the transfusion. The total amounts of the metabolites and hormones infused and removed from the infant were calculated. The infusion of glucose in blood preserved with acid citrate and glucose caused a rise in plasma glucose, insulin, and growth hormone levels and a fall in plasma free fatty acid levels. The plasma glycerol levels did not change significantly during transfusions with blood preserved with acid citrate and glucose, or acid citrate alone. In both types of exchange transfusion there was a similar gradual fall in plasma glucagon concentration and net loss of free fatty acid, glycerol, and glucagon. A net loss of growth hormone occurred which was greater in transfusions performed with blood preserved with acid citrate and glucose than in transfusions performed with blood preserved with acid citrate. In transfusions performed with blood preserved with acid citrate and glucose there was a net accumulation of glucose by the infant and a net loss of insulin.